Efectos de la implementación del Sistema de Gestión de la Calidad bajo el modelo NTC-ISO 9001 en la Gestión del Recurso Humano (2012)
The quality of goods and services and customer lo- yalty upon which any public or private organization, industrial or search for services, depends largely on the real commitment of the people within the orga- nization. This article makes an analytical contribution to organizational reality subsequent to the ISO 9001 certification, identifying the effects that the imple- mentation of quality management cause in relation to the development of the skills of the people and in the talent management model and its contribution to the evaluation of the effectiveness of that system of quality management.Based on the series of ISO 9000 norms seven catego- ries were defined to study the effects on the human resource exercised by the system of the implemen- tation of quality management: Managing directors; Involvement of people; Management documentary work environment; Performance competency-based staff, communication and continuous improvement. From these categories tools of inquiry were develo- ped which were implemented in the education sector. As a result of the investigation it was found that for- mation and training, linked to the real needs of the organization, are a great positive effect that has left the implementation of a system of quality management, and likewise has raised awareness about the importan- ce of documentation and the possibility to always im- prove the work done. There is no visible impact on the effectiveness of internal communication processes, so we must rethink the methods used during deployment to address this issue.